Model of psychological readiness of a coach to make decisions in extreme situations of professional activity - Khurtenko, O.; Liebiedieva, S.; Perelygina, L.; Morhunov, O. A.; Моргунов, О. А.; ORCID: http://orcid.org/0000-0003-2259-3620; Ovcharuk, V.; Mykhliuk, E. (BRAIN. Broad Research in Artificial Intelligence and Neuroscience. – 2022. – Vol. 13, Issue 1, Sup.1. – P. 247-266, 2022)
Завищена самооцінка провокує встановлення цілей вище реальних можливостей, нехтування необхідною інформацією, зниження ймовірності невдачі, мінімізацію зусиль для досягнення мети, «розслаблюючий» ефект успіху та сильне емоційне переживання невдачі; потреба підтримувати рівень самооцінки призводить до охоронного ігнорування невдач, пояснення їх зовнішніх причин, що послаблює стимул до їх подолання. Різко завищена самооцінка може створити на певному етапі діяльності зону постійних невдач, зниження професійної мотивації. Наслідком низької самооцінки є пасивність, страх відповідальності, схильність ставити надто легкі завдання, недооцінка суб'єктивної ймовірності успіху, що порушує вплив невдач. Очевидно, що неадекватність самооцінки стає перешкодою для професійної адаптації. Як свідчать наші спостереження, характерно, що тренери, які не володіють достатнім рівнем компетентності в управлінні підлеглими, мають завищену самооцінку. Але й адекватна висока самооцінка, яка спонтанно формується в процесі професійної підготовки, може стати дезорганізуючим фактором, якщо її критично не перенести з навчальної діяльності в професійну. У цьому випадку входження в професійну діяльність, яка вже характеризується зниженням стійкості самооцінки, ускладнюється її сильними коливаннями. Крім того, ми виявили, що немає суттєвої кореляції між успішністю навчання та успішністю початку професійної діяльності. Завищена самооцінка молодого спеціаліста часто є перешкодою для прийняття його в колектив. Інтерференцією на цьому етапі є творчий адаптивний компонент, який переважає над конформним.

Inflated self-esteem provokes goal setting higher than the real possibilities, neglect of the necessary information, reduction of the probability of failure, minimization of efforts to achieve the goal, "relaxing" effect of success and a strong emotional experience of failure; the need to maintain the level of self-esteem leads to a protective ignoring of failures, the explanation of their external causes, which weakens the incentive to overcome them. Sharply inflated self-esteem can create at a certain stage of activity a zone of constant failures, reduced professional motivation. The consequence of low self-esteem is passivity, fear of responsibility, tendency to set too easy tasks, underestimation of the subjective probability of success, which disrupts the impact of failures. Obviously, the inadequacy of self-esteem becomes an obstacle to professional adaptation. As evidenced by our observations, it is characteristic that coaches who do not have a sufficient level of competence in the management of subordinates, have an inflated self-esteem. But also adequate high self-esteem, which is spontaneously formed in the process of professional training, can become a disorganizing factor, if it is not critically transferred from educational to professional activities. In this case, entering a professional activity, which is already characterized by a decrease in the stability of self-esteem, is complicated by its strong fluctuations. In addition, we found that there is no significant correlation between learning success and success in starting a professional activity. High self-esteem of a young specialist is often an obstacle to his acceptance into the team. The creative adaptive component, which prevails over the conformal one, is an interference at this stage.

Завышенная самооценка провоцирует постановку цели выше реальных возможностей, пренебрежение необходимой информацией, снижение вероятности неудачи, минимизацию усилий для достижения цели, «расслабляющий» эффект успеха и сильное эмоциональное переживание неудачи; необходимость поддержания уровня самооценки приводит к защитному игнорированию неудач, объяснению их внешних причин, что ослабляет стимул к их преодолению. Резко завышенная самооценка может создать на определенном этапе деятельности зону постоянных неудач, сниженную профессиональную мотивацию. Следствием низкой самооценки является пассивность, боязнь ответственности, склонность ставить слишком легкие задачи, недооценка субъективной вероятности успеха, что сводит на нет влияние неудач. Очевидно, что неадекватность самооценки становится препятствием для профессиональной адаптации. Как свидетельствуют наши наблюдения, характерно, что тренеры, не обладающие достаточным уровнем компетентности в управлении подчиненными, имеют завышенную самооценку. Но и адекватная высокая самооценка, стихийно формирующаяся в процессе профессиональной подготовки, может стать дезорганизующим фактором, если критически не переносить ее с учебной на профессиональную деятельность. В этом случае вхождение в профессиональную деятельность, для которой уже характерно снижение устойчивости самооценки, осложняется ее сильными колебаниями. Кроме того, мы обнаружили отсутствие значимой корреляции между успешностью обучения и успешностью начала профессиональной деятельности. Высокая самооценка молодого специалиста часто является препятствием для его принятия в коллектив. Интерференцией на данном этапе является творческий адаптивный компонент, преобладающий над конформным.
Model of psychological readiness of a coach to make decisions in extreme situations of professional activity / Oksana Khurtenko, Svitlana Liebiedieva, Lina Perelygina, Oleksandr Morhunov, Vasyl Ovcharuk, Eduard Mykhliuk // BRAIN. Broad Research in Artificial Intelligence and Neuroscience. – 2022. – Vol. 13, Issue 1, Sup.1. – P. 247-266. – DOI: https://doi.org/10.18662/brain/13.1Sup1/317.
Khurtenko, O., Liebiedieva, S., Perelygina, L., Morhunov, O., Ovcharuk, V., & Mykhliuk, E. (2022). Model of Psychological Readiness of a Coach to Make Decisions in Extreme Situations of Professional Activity. BRAIN. Broad Research in Artificial Intelligence and Neuroscience, 13(1Sup1), 247-266. https://doi.org/10.18662/brain/13.1Sup1/317.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; publikatsii u WoS; психологічна готовність; тренер; прийняття рішень; екстремальні професійні ситуації; coach readiness model; inflated self-esteem; motivation of the coach activity; professional training; young specialists; management of subordinates; модель готовності тренера; завищена самооцінка; мотивація діяльності; професійна підготовка; молоді спеціалісти; управління підлеглими; психологическая готовность; принятие решений; extreme professional situations; экстремальные профессиональные ситуации